Taking Stock of Industrial Ecology 2016
DOI: 10.1007/978-3-319-20571-7_2
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Models of Society’s Future Metabolism: What Industrial Ecology Has to Contribute

Abstract: Scientifi c assessment of sustainable development strategies provides decision-makers with quantitative information about the strategies' potential effect. This assessment is often done by forward-looking or prospective computer models of society's metabolism and the natural environment. Computer models in industrial ecology (IE) have advanced rapidly over the recent years, and now, a new family of prospective models is available to study the potential effect of sustainable development strategies at full scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 69 publications
0
31
0
Order By: Relevance
“…These approaches share a common origin, and their formal differentiation is still being debated within the LCA community (Bjørn et al. ; Pauliuk and Hertwich ). It is traditionally acknowledged that ALCA and CLCA aim to answer different questions: “What environmental impact can be attributed to product X?” and “what environmental impact is product X responsible for?” (Bjørn et al.…”
Section: Methodsologymentioning
confidence: 99%
See 1 more Smart Citation
“…These approaches share a common origin, and their formal differentiation is still being debated within the LCA community (Bjørn et al. ; Pauliuk and Hertwich ). It is traditionally acknowledged that ALCA and CLCA aim to answer different questions: “What environmental impact can be attributed to product X?” and “what environmental impact is product X responsible for?” (Bjørn et al.…”
Section: Methodsologymentioning
confidence: 99%
“…approaches exist in LCA (Earles and Halog 2011): ALCA and CLCA. These approaches share a common origin, and their formal differentiation is still being debated within the LCA community (Bjørn et al 2017;Pauliuk and Hertwich 2016). It is traditionally acknowledged that ALCA and CLCA aim to answer different questions: "What environmental impact can be attributed to product X?"…”
Section: Introductionmentioning
confidence: 99%
“…It has been applied to steel (Hatayama et al 2010;Pauliuk et al 2013) and aluminum (Liu et al 2012). The approach was refined to allow for the study of critical materials ), but it has not yet been applied to potentially critical metals on the global scale.…”
Section: Existing Approaches To Estimate Future Metal Flows and Resoumentioning
confidence: 99%
“…Regional resource scarcity, regional production capacity, regional policies, and international political relations strongly influence future availability and trade patterns for critical materials (European Commission 2010). To anticipate possible future development, one needs prospective assessment of the anthropogenic cycles of specialty metals (Pauliuk and Hertwich 2015), without attempting to predict the future. A scenario analysis of future supply of critical metals is a more modest and scientific approach than a prediction; it enables researchers and policy makers to study the consequences of future economic development on metal reserves and possible futures and supply shortages in different regions.…”
mentioning
confidence: 99%
“…Their work revealed that LCA metrics carry crucial information that needs to be considered by both energy system modelers and climate policy makers. Currently, life cycle metrics are rarely considered in integrated assessment models (Pauliuk and Hertwich 2016;Pauliuk et al 2017), although some studies aim to cover this gap for greenhouse gas (GHG) emissions (Daly et al 2015;Pehl et al 2017;McDowall et al 2018) and for other life cycle impacts (Arvesen et al 2018).…”
Section: Introductionmentioning
confidence: 99%